Experimental Investigation of Piles Behaviour Subjected to Lateral Soil Movement - Ozcelik Ersoy, Cigdem; Yildirim, Sonmez (TURKISH CHAMBER CIVIL ENGINEERS, 2014)
In this study, the behaviour of vertical piles installed in order to increase slope stability under lateral soil movement is observed by model tests conducted in a specially built large scale shear box in the geotechnics laboratory of Yildiz Technical University. Laboratory model tests were carried out on sandy soil slopes stabilized with piles. A row of four 800 mm long aluminum pipes with a diameter of 35 mm and wall thickness of 5 mm were used. Pile heads were connected to each other by means of an aluminum beam. The single pile row was subjected to the loading due to lateral soil movement and deformations and bending moments developed in the pile sections were measured by strain gauges attached at different points along the pile lengths. The results obtained from the experiments are compared with the methods found in the literature in order to make a contribution to a better understanding of this complicated geotechnical problem.
Keywords: Slope stability; lateral soil movement; pile; large scale shear box; STABILITY; Engineering